(3OjhGf TYQs
(3ChdgG (B:s
(3hYjS NWJ YQV GdadG HQMGdfG JRYRY aj GdCYfGb QbT GdJeGFe EPG aGM QjYGf GdfSje QCjJgG Edi GdLGfH GdZQHj YhL GdNjGTe s
(3BNQgG (B:s
(3hBNQ eG ajgG(B: (3aj eLdS bqhe CYWGag oJbGQH GdhUd hbQH GdfYje s
(3GdehLhO efg bWYI eHJhQI GdChd hGdBNQ ef hQbI (B117 (3MJi (B120s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B132 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdCOHs